Comparative Efficacy of Low Dose vs High Dose Sildenafil in Treatment of Pulmonary Hypertension in Neonates - Malik, Hafiz Zeekash Ur Rehman; Shahzad, Muhammad; Younus, Javaria; Riaz, Mayda; Haron, Farah; Tariq, Bushra (Indus Journal of Bioscience Research, 2025)
Background: Persistent Pulmonary Hypertension of the Newborn (PPHN) is a life-threatening condition caused by increased pulmonary vascular resistance, leading to right-to-left shunting of blood and severe hypoxemia. Objective: To compare the efficacy of low dose sildenafil with that of high dose in treatment of PPHN. Methods: This experimental study was conducted at the Neonatology Department of the Children’s Hospital and University of Child Health Sciences, Lahore. 60 neonates diagnosed with PPHN within the first week of life were enrolled. Patients were administered sildenafil orally, starting at 0.5 mg/kg every six hours. The dose was gradually titrated to 2 mg/kg based on oxygen saturation and clinical stability. Key outcomes included improvements in oxygen saturation, echocardiographic measures, and the incidence of adverse effects. Results: Sildenafil treatment significantly improved oxygen saturation in neonates with pulmonary hypertension. The Wilcoxon Signed-Rank Test showed a statistically significant increase in oxygen saturation after treatment. A Mann-Whitney U Test comparing low-dose (0.5 mg/kg) and high-dose (2 mg/kg) groups revealed no significant difference in post-treatment oxygen saturation (p = 1.000). The Spearman’s Rank Correlation test confirmed no correlation between sildenafil dose and oxygen saturation before (ρ = 0.000, p = 1.000) or after treatment (ρ = 0.000, p = 1.000). Additionally, a Chi-Square test found no significant relationship between sildenafil dose and side effects such as hypotension, hypokalemia, anemia, or bradycardia, with all p-values greater than 0.05. Conclusion: Sildenafil effectively increases oxygen saturation in neonates with pulmonary hypertension. Results indicate that increasing sildenafil dose does not provide additional benefits in oxygen saturation or in reducing side effects, supporting the use of lower doses in clinical practice.